MANAGEMENT INFORMATION SYSTEMS IN THE COMPLEX OF MARKETING SUPPORT OF PRODUCT QUALITY IN THE AI ECONOMY - Marina O. Omurbekova; Mukaddas A. Dzhorobaeva; Zhumagul K. Umarbekova; Tulkin Z. Teshabaev; Elena G. Popkova (Proceedings on Engineering Sciences, 2025)
We performed a comprehensive analysis of the indicators and efficiency of implementing management information systems in the complex of marketing support of product quality in the AI economy. The research object is intellectual marketing information systems, which are used in the world market, namely SugarCRM Inc. (system for multifunctional automatization of marketing support); KISSmetrics and Google Analytics (systems for expanded marketing analytics); Exponea, SharpSpring, and HubSpot (systems for improvement or organisation of bilateral relationships with the customer). In the course of the analysis, we determined the advantages of the considered marketing information systems and established the connection between the growth of the number of consumers and the level of sales in the world markets. The main channel of promotion of these systems is connected with paid promotion packages. We proved that to support the economy and promote the AI economy it is necessary to help small businesses in the context of implementing modern intellectual marketing information systems, which ensure the promotion of information about product quality. The scientific novelty of this research consists in the systematisation of advantages of modern intellectual marketing information systems, which ensure the quality of the promoted products. The objective of this research was to identify the features and effectiveness of the existing management information systems, which are used in the complex of marketing support of product quality in the AI economy.